Peran Guru Pendidikan Agama Islam dalam Meningkatkan Akhlakul Karimah Siswa (Penelitian Kualitatif di SMP Bhakti Mandiri Pasirwangi, Garut) - Jamaludin, Rudi; Nasrullah, Yufi Mohammad; Anton, Anton (LANCAH: Jurnal Inovasi dan Tren, 2025)
The purpose of this study aims to determine the role of Islamic religious education teachers at SMP Bhakti Mandiri Garut, what are the supporting and inhibiting factors in improving student morals, what solutions are provided by Islamic religious education teachers in dealing with students who are less disciplined. This study uses a descriptive method with a qualitative approach. This research was conducted at SMP Bhakti Mandiri Garut. The data sources used in this study are primary data sources and secondary data sources. The data collection techniques used by researchers are observation, interviews and documentation. While the data analysis techniques used follow the concept of Miles and Huberman, namely the data reduction stage, data presentation, and drawing conclusions. From the results of this study, it can be concluded that the role of Islamic religious education teachers is very helpful for schools in achieving the goals that have been detailed and set by the school. The role of Islamic Education teachers at SMP Bhakti Mandiri is not only to carry out general teacher duties but has a larger portion and responsibility, namely increasing moral values for students, by teaching, guiding and habituating positive values for students. Supporting and inhibiting factors in improving students' morals include a lot of support from the school, for example by giving Islamic Religious Education teachers the freedom to package learning and guidance in such a way. The inhibiting factors are limited time and student relationships. The role of Education teachers in providing solutions to improve students' morals, with this it can be seen how teachers do it, namely by providing various guidance, habits that have positive values for students.